2021
DOI: 10.3389/fnut.2021.608972
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Protein Patterns During Pregnancy and the Risk of Infant Eczema: A Cohort Study

Abstract: Background: Previous studies have suggested that maternal dietary protein was associated with allergic diseases in offspring, but few studies have evaluated the influence of dietary protein patterns. This study aimed to explore the prospective association between maternal dietary protein patterns during pregnancy and the risk of infant eczema.Methods: A total of 713 mother-child pairs from a prospective cohort in Guangzhou, China were recruited. Maternal dietary protein was estimated using a validated face-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 70 publications
1
5
4
Order By: Relevance
“…While high‐quality carbohydrate, like whole grains, have lots of bioactive components (such as fiber, vitamins, and minerals), except for macronutrients. Additionally, it was found that protein, probably animal protein, had a protective effect on allergic diseases, which is contrary to the results of another study in Guangzhou, China 30 . The reason for inconsistent results might be the different maternal average intake of animal protein, with an energy of 5.5% in our study and 8.9% in that study 30 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While high‐quality carbohydrate, like whole grains, have lots of bioactive components (such as fiber, vitamins, and minerals), except for macronutrients. Additionally, it was found that protein, probably animal protein, had a protective effect on allergic diseases, which is contrary to the results of another study in Guangzhou, China 30 . The reason for inconsistent results might be the different maternal average intake of animal protein, with an energy of 5.5% in our study and 8.9% in that study 30 .…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, it was found that protein, probably animal protein, had a protective effect on allergic diseases, which is contrary to the results of another study in Guangzhou, China 30 . The reason for inconsistent results might be the different maternal average intake of animal protein, with an energy of 5.5% in our study and 8.9% in that study 30 . Besides, we found higher animal fat intake was associated with a higher risk of allergic diseases.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Four kinds of protein were determined: proteins found in red meat, fish, poultry, plants, dairy, and eggs. Eczema risk was found to be higher in the group with high poultry consumption compared with the other dietary protein patterns, and a lower incidence of infant eczema at six months was found [ 20 ]. This outcome was consistent with a prior Australian study showing a positive correlation between maternal pre-conception poultry ingestion and offspring atopic dermatitis [ 53 ].…”
Section: Reviewmentioning
confidence: 99%
“…In this context, dietary protein patterns (DPPs) appear alluring. However, few studies have embraced this approach to evaluate the relationship between protein intake and specific health outcomes [ 19 , 21 , 22 , 23 , 24 ]. Meanwhile, to our knowledge, there are no data regarding the associations between maternal dietary protein food patterns and neonatal anthropometrics.…”
Section: Introductionmentioning
confidence: 99%